Recent topics of phosphine-mediated reactions. Issue 2 (10th January 2018) - Karanam, Praneeth; Reddy, Ganapuram Madhusudhan; Koppolu, Srinivasa Rao; Lin, Wenwei
Graphical abstract: Highlights: Recent advances in stoichiometric phosphine-mediated reactions have been summarized. Phosphines have excellent nucleophilicity, oxyphilicity, basicity and leaving group ability. Recent reports are categorized based on type of intermediate/reaction involved. This review provides good insight of recent research and future perspectives. Abstract: Phosphines constitute key organophosphorus reagents that are being widely used in industry as well as in research laboratories since over a century. Specifically, in last two decades, there have been numerous reports on phosphine-mediated and phosphine-catalyzed reactions. In terms of industrial application, phosphine-mediated reactions have received much attention when compared to the catalytic versions for the synthesis of a variety of structurally diverse organic frameworks. In this digest review, we wish to summarize the recent advances (2014–2017) in phosphine-mediated reactions that are primarily based on stoichiometric application of phosphine.